Effective long term adaptation and metabolic state regulation of ski-racers - Bakhareva, A.S.; Isaev, A.P.; Erlikh, V.V.; Aminov, A.S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to scientifically substantiate effective mechanisms of organism’s bio-chemical adaptation of ski-racers in competition period with the help of lipid peroxidation indicators, oxidative modification of proteins and activity of hypothalamus pituitary adrenocortical system. Material: in the research 14 sportsmen of 18-25 years’ age (combined team of university) with different level of sportsmanship participated. Assessment of free radical oxidation, anti-oxidant system, cortisol level was fulfilled with the help of indicators’ quantitative analysis by bio-chemical methods applied to blood serum samples. Results: it was found that in the basis of bio-chemical changes under intensive physical loads is increase of catabolic processes’ speed. Change of organism’s metabolic orientation of ski racers at optimal level results in working muscles’ energy supply improvement, increase of energy systems’ power and sports efficiency. Conclusions: Application of interval trainings at stages of preparation to special significant competitions results in expected adaptation and increase of sports efficiency. We also showed their effective role in ensuring long term reactions, conditioning high sports efficiency.